Challenges and Best Practices in Security Configuration for Containerized Environments - Venkat Marella, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Through an analysis of theoretical frameworks, best practices, innovations, and problems, this research study delves into the complex field of Configuration Management (CM) in the current day. The fundamental knowledge of CM is formed by theoretical models, such as ITIL and the Three-Component Model, which direct the efficient identification, control, and status accounting of configuration items. Traditional CM approaches are being reshaped by innovations like DevOps integration, Infrastructure as Code (IaC), and containerization technologies, which provide solutions for scalability, automation, and flexibility. In a multi-cloud setting, containerization enables resource optimization and workload mobility. In recent years, containerization in multi-cloud systems has drawn a lot of interest from both academic and industry development viewpoints. In order to improve cyber safety in containerized systems, the research examines the comparative analysis of security solutions, difficulties, and best practices. In order to investigate safety flaws in containerization platforms, investigate methods for enhancing container isolation, and evaluate the critical role encryption techniques play in delivering secure applications, this review aims to shed light on the improved security posture of containerized environments. Additionally, the report offers helpful advice for companies looking to bolster their cyber security defences on containerization systems.
Keywords: Infrastructure as Code (IaC); Containerization; Organizations; Industrial Development; Configuration Management (CM); Optimized Resource Utilization; Cloud Environment; Automation; Cyber Safety; Three-Component Model; DevOps Integration